Hybrids of RNA viruses and viroid-like elements replicate in fungi - Forgia, Marco; Navarro, Beatriz; Daghino, Stefania; Cervera, Amelia; Gisel, Andreas; Perotto, Silvia; Aghayeva, Dilzara N.; Akinyuwa, Mary F.; Gobbi, Emanuela; Zheludev, Ivan N.; Edgar, Robert C.; Chikhi, Rayan; et al. (Nature communications, 2023)
Earth’s life may have originated as self-replicating RNA, and it has been argued that RNA viruses and viroid-like elements are remnants of such pre-cellular RNA world. RNA viruses are defined by linear RNA genomes encoding an RNA-dependent RNA polymerase (RdRp), whereas viroid-like elements consist of small, single-stranded, circular RNA genomes that, in some cases, encode paired self-cleaving ribozymes. Here we show that the number of candidate viroid-like elements occurring in geographically and ecologically diverse niches is much higher than previously thought. We report that, amongst these circular genomes, fungal ambiviruses are viroid-like elements that undergo rolling circle replication and encode their own viral RdRp. Thus, ambiviruses are distinct infectious RNAs showing hybrid features of viroid-like RNAs and viruses. We also detected similar circular RNAs, containing active ribozymes and encoding RdRps, related to mitochondrial-like fungal viruses, highlighting fungi as an evolutionary hub for RNA viruses and viroid-like elements. Our findings point to a deep co-evolutionary history between RNA viruses and subviral elements and offer new perspectives in the origin and evolution of primordial infectious agents, and RNA life. RNA viruses are defined by linear RNA genomes encoding an RNA-dependent RNA polymerase, while viroid-like elements consist of small, single-stranded, circular RNA genomes that, in some cases, encode self-cleaving catalytic RNAs. Here, the authors identify over 20,000 candidate viroid-like elements, and show that infectious agents of fungi display hybrid features of viroid-like RNAs and RNA viruses.